2006
DOI: 10.1128/iai.00757-06
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma japonicum Reinfection after Praziquantel Treatment Causes Anemia Associated with Inflammation

Abstract: There is a relationship between schistosomiasis and anemia, although the magnitude and exact mechanisms involved are unclear. In a cohort of 580 Schistosoma japonicum-infected 7-to 30-year-old patients from Leyte, The Philippines, we evaluated the impact of reinfection with S. japonicum after treatment with praziquantel on the mean hemoglobin level, iron-deficiency (IDA) and non-iron-deficiency anemia (NIDA), and inflammatory markers. All participants were treated at baseline and followed up every 3 months for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 37 publications
3
70
0
Order By: Relevance
“…Successful treatment of anemia in this setting should rely on strategies based on this and other evidence of infectionrelated AI frequency. Our findings, combined with those of other recent studies, 6,25,28,29 suggest that both chronic infection and iron deficiency need to be addressed as part of integrated management of childhood anemia.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Successful treatment of anemia in this setting should rely on strategies based on this and other evidence of infectionrelated AI frequency. Our findings, combined with those of other recent studies, 6,25,28,29 suggest that both chronic infection and iron deficiency need to be addressed as part of integrated management of childhood anemia.…”
Section: Discussionsupporting
confidence: 53%
“…What has become more evident over the last decade is that chronic inflammation caused by long-lasting parasitic infections appears to strongly reduce the body's ability to absorb dietary iron (via gut ferroportin) and to use existing body iron stores for erythropoiesis. 6,25 Infection-related AI has been strongly linked to the presence of subclinical infection, both for children with subclinical malaria in Cote d'Ivoire, 6 and for Philippine children having persistent or recurrent low-level Schistosoma japonicum infection after praziquantel therapy. 25,26 Our current study of the mechanisms of anemia associated with prevalence parasitic infections suggests that AI combined with true iron deficiency is the primary source of childhood anemia in this area of coastal Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…Given the rapid increase after treatment without provision of iron in most studies, much of that improvement is likely caused by amelioration of S. japonicum -related anemia of inflammation. 16,25 It is possible, however, that some of the sustained improvement in hemoglobin found in other studies may be caused by reduction in hookworm burden. Interestingly, a previous study conducted in Leyte, The Philippines, showed that coinfection with S. japonicum and hookworm had a Hookworm: low = 1-1,999 eggs per gram of stool (epg), moderate = 2,000-3,999 epg, high ≥ 4,000 epg.…”
Section: Discussionmentioning
confidence: 52%
“…There is increased awareness due to the media as well. 9 "The burden of iron deficiency can be reduced by taking a more holistic approach that would include promotion of healthy weaning practices and use of appropriate complementary foods, together with improving the nutritional value of such foods. There is an increasing body of peer-reviewed literature to support the contention that "micronutrient Sprinkles" is an effective strategy to improve the nutritional value of home-prepared complementary foods and thus to reduce the burden of iron deficiency among children".…”
Section: Resultsmentioning
confidence: 99%